Software testing for reliability and quality improvement - Bajjouk, Mouad; Ramachandiran, Chandra Reka; Rana, Muhammad Ehsan; Chelliah, Sivananthan (Journal of Applied Technology and Innovation, 2021)
Software systems are hard to complete as customers became hard to satisfy and their requirements are more complicated. In this paper, quality factors that affect software are discussed, with some well-known standards that improve and assist while planning for quality assurance. The testing strategies and types that contribute to improving quality are also highlighted. A development methodology was mentioned as it gives more support to the testing phase.